(untitled) (Annals of Medical Research, 2021)
Aim: We investigated the development of epistaxis and the effect of red blood cell distribution (RDW) and mean platelet volume (MPV) levels in hypertensive patients compared to non-hypertensive patients. Epistaxis is an urgent rhinologic condition that may manifest itself as recurrent hemorrhages in small quantities or life-threatening hemorrhages. It is known that epistaxis does not develop in every hypertensive patient.Material and Methods: In this retrospective study, the participants were divided into four groups as follows: Group 1 hypertensive epistaxis, Group 2 isolated epistaxis, Group 3 isolated hypertension, Group 4 control. RDW and MPV values were obtained from complete blood count (CBC) samples.Results: There was a statistically significant difference in RDW and MPV blood parameters between all groups (p=0.02). When RDW and MPV blood parameters of Group 1 with hypertensive epistaxis and Group 3 with isolated hypertension were evaluated, there was a statistically significant difference between these two groups in both parameters (p = 0.000, p = 0.011).Conclusion: In our study, we showed that the decrease in RDW and MPV values among the hematological parameters increases the association of epistaxis with hypertension in hypertensive patients compared to non-hypertensive patients.